2015
DOI: 10.1542/peds.2014-1755
|View full text |Cite
|
Sign up to set email alerts
|

Presepsin for the Detection of Late-Onset Sepsis in Preterm Newborns

Chiara Poggi,
Tommaso Bianconi,
Elena Gozzini
et al.

Abstract: BACKGROUND: Late-onset sepsis (LOS) is among the leading causes of morbidity and mortality in preterm newborns, and currently available diagnostic tools are inadequate. The objective of this study was to evaluate the accuracy of presepsin (P-SEP) as novel biomarker of bacterial infection for the diagnosis of LOS in preterm newborns. METHODS:We prospectively studied newborns #32 weeks' gestational age with LOS (n = 19) and noninfected controls (n = 21) at 4 to 60 days' postnatal age. At enrollment, and 1, 3, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 31 publications
7
60
0
1
Order By: Relevance
“…These results agree with Poggi C et al [5] who found that CRP utility is questionable because its peak values are reached only after a 2-to 3-day delay after the infective stimulus, and its value can increase after non-infective inflammatory events.…”
Section: Late-onset Neonatal Sepsis (Los) Is a Life-threatening Condisupporting
confidence: 91%
See 2 more Smart Citations
“…These results agree with Poggi C et al [5] who found that CRP utility is questionable because its peak values are reached only after a 2-to 3-day delay after the infective stimulus, and its value can increase after non-infective inflammatory events.…”
Section: Late-onset Neonatal Sepsis (Los) Is a Life-threatening Condisupporting
confidence: 91%
“…These results were close to Poggi C et al [5] results who found that The area under the ROC curve for Presepsin was 0.972 (95% confidence interval [CI] 0.92-1.00) and that presepsin achieved the best accuracy for prediction of probable sepsis at the cutoff of 885 ng/L with 94% sensitivity (95% CI 74-100) and 100% specificity (95% CI 84-100). The positive and negative predictive values were 100% (95% CI, 83-100) and 95% (95% CI, 80-100).…”
Section: Late-onset Neonatal Sepsis (Los) Is a Life-threatening Condisupporting
confidence: 88%
See 1 more Smart Citation
“…We determined low cut off levels and weak specificity and PPV in contrast to good sensitivity and high NPV. There are only few existing paediatric studies focused on analysis of presepsin's diagnostic usefulness, mainly in newborns [18,21]. Papers considered febrile episodes in childhood oncology patients reported also inconclusive results [17,20].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, another study suggested presepsin as an accurate biomarker for the diagnosis of possible LOS. In this study, authors also stated that it might provide useful information for monitoring response to therapeutic interventions [20]. Mussap et al [21] investigated presepsin levels of neonates with severe disease, and they could not determine any correlation between gestational age and presepsin levels.…”
Section: Presepsin and Sepsis In Neonatesmentioning
confidence: 79%